Penguatan Sikap Anti Korupsi Pada Guru Dan Siswa Di SMP Islam Terpadu Bina Amal Gunungpati Semarang - Eko Handoyo; Natal Kristiono; Eta Yuni Lestari; Wahyu Benny MS; Maryam Maryam; Bambang Wiwitono; Fahrudin Lutfi Ahmad; Ludia Alfafa Faza (CV. Aksara Global Akademia, 2024)
The problem of corruption in Indonesia has become a public conversation, both through the news, electronic media and social media. This is related to corruption cases and corrupt behavior that occurs everywhere. In fact, in almost all regions of Indonesia with various types and modes. Corrupt behavior has penetrated every element of the nation, even though we all know that corruption is immoral behavior. The large number of corruption cases requires efforts to prevent them, one of which is by strengthening anti-corruption attitudes. Strengthening anti-corruption attitudes is one way of education in forming a mental attitude in a person who is structured to behave anti-corruption. The aim of strengthening anti-corruption attitudes is broad and comprehensive depending on age, education and environment, as long as a person is able and able to receive character education. The importance of strengthening anti-corruption attitudes at SMP IT Gunungpati among teachers and students has led the Semarang State University service team to help overcome this problem by strengthening anti-corruption attitudes among students in the form of service